PENGARUH KUALITAS LAYANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PENGGUNAAN PADA E-COMMERCE TOKOPEDIA (PENELITIAN PADA GENERASI MILENIAL DI JAKARTA) - Gusti Pangestu, (2021)
The purpose of this study was to determine the effect of service quality and brand image on the decision to use Tokopedia e-commerce in the millennial generation in the DKI Jakarta area. The approach used in this research is quantitative with the population, namely Tokopedia e-commerce consumers who are included in the millennial generation and live in the DKI Jakarta area. The sample used was 100 samples, where the sample was determined using a non-probability sampling technique with purposive sampling method. Data collection is done by distributing questionnaires via google form. The data processing tool used is PLS (Partial Least Sqaure). The results show that : (1) service quality has an effect on usage decisions. (2) brand image influences usage decisions.